Mycobiota on exoskeleton debris of Neohelice granulata in an alkaline-sodic salt marsh : In vitro enzyme ability at different temperatures and pH - Ferreri, Natalia Analía (2021)
This study analysed the mycobiota on exoskeleton debris of the crab Neohelice granulata collected from an alkaline salt marsh and assessed the in vitro enzyme ability of selected isolates at different temperatures and pH. Exoskeleton fragments were incubated in moist chambers on paper and on agar medium. Growth and enzyme ability of selected fungi were also evaluated in agar media with 0.5 % casein, 1% Tween®20, and Chitin-Azure® by the production of a halo/growth ratio. We identified 22 fungal species using both methods. Since the two isolation methods added information to one another, both ones are necessary to recover the cultivable mycobiota associated with the exoskeleton debris. All fungi showed greater levels of enzyme activity in alkaline than acid medium with Tween®20. The halo diameter on casein and chitin varied according to the fungal isolate and pH. Most fungi had a larger halo at 4°C than at the other temperatures tested. Clonostachys rosea showed the greatest activity in all media at 4oC. We conclude that exoskeletons of the N. granulata are a source of fungi able to produce enzyme activities that show differences upon incubation conditions to which they are cultivated such as ones including specific temperatures and pH values.